Performance Analysis of Protected Fund and Equity Fund Using Sharpe, Treynor, Jensen - Ningrum, Mersa Lestari; Risman, Asep (Universitas Mercu Buana, 2022)
This study was conducted to determine the mutual funds' performance of capital-protected and equity funds from February 2021 to August 2021. Return, risk, Sharpe index, Treynor index, and Jensen index are all used to evaluate mutual fund performance. Sample data consisted of 462 capital-protected fund products and 273 equity fund products. The performance of equities funds outperforms that of capital-protected funds, according to the average Sharpe index. The Treynor index showed that capital-protected funds outperformed the market. The Jensen index shows that capital-protected funds outperform equity funds. In March, April, and May, capital-protected funds outperform the market (JCI), whereas equities funds outperform in April and August. In April, capital-protected funds outpaced risk-free investments, whereas equity funds outperformed in February, July, and August. The Independent T-Test is the statistical approach used to test the hypothesis. The findings revealed no substantial differences between capital-protected funds and equity funds, allowing investors to invest in one or both.